2008
DOI: 10.1371/journal.pgen.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Genetic Structure and Social Organization in Central Asia: Insights from a Multi-Locus Study

Abstract: In the last two decades, mitochondrial DNA (mtDNA) and the non-recombining portion of the Y chromosome (NRY) have been extensively used in order to measure the maternally and paternally inherited genetic structure of human populations, and to infer sex-specific demography and history. Most studies converge towards the notion that among populations, women are genetically less structured than men. This has been mainly explained by a higher migration rate of women, due to patrilocality, a tendency for men to stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 66 publications
4
112
0
Order By: Relevance
“…33,34 To avoid any bias of geographic structure in the sampling, we first identified four distant areas where farmer and herders coexist nowadays (Middle-East, Pakistan, Russia and East Asia), and then selected randomly one traditionally nomadic herder population and one neighboring sedentary farmer population from each of these regions Table S1). We used 21 autosomal microsatellites markers out of the 27 markers selected by Ségurel et al 35 from the HGPD-CEPH panel (Supplementary Table S2). We removed indeed six loci (GATA22F11, GATA88H02, SE30, GATA28D01, GATA11B12 and GATA12A07) from the original data set as they presented compound repeat motives, and might thus not fit the assumption of a SSM (single stepwise model).…”
Section: Population Sampling and Marker Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 To avoid any bias of geographic structure in the sampling, we first identified four distant areas where farmer and herders coexist nowadays (Middle-East, Pakistan, Russia and East Asia), and then selected randomly one traditionally nomadic herder population and one neighboring sedentary farmer population from each of these regions Table S1). We used 21 autosomal microsatellites markers out of the 27 markers selected by Ségurel et al 35 from the HGPD-CEPH panel (Supplementary Table S2). We removed indeed six loci (GATA22F11, GATA88H02, SE30, GATA28D01, GATA11B12 and GATA12A07) from the original data set as they presented compound repeat motives, and might thus not fit the assumption of a SSM (single stepwise model).…”
Section: Population Sampling and Marker Setsmentioning
confidence: 99%
“…Among these populations, 26 had been genotyped in previous studies 35,37 for the same 21 markers that we used for the HGDP Eurasian populations (Supplementary Table S2). The four other populations (KIB, TAB, KIM and TAM) were genotyped for this study, using the same PCR and genotyping procedures (see below).…”
Section: Population Sampling and Marker Setsmentioning
confidence: 99%
“…In humans, cultural differences, such as language or religious beliefs, may play an additional role in shaping structure among individuals (Cavalli-Sforza and Feldman 2003;Behar et al 2010;Bryc et al 2010). Large efforts have been made to characterize population structure, both at the global level (e.g., Rosenberg et al 2002;Jakobsson et al 2008;Li et al 2008) and at smaller scales (e.g., Rosenberg et al 2006;Wang et al 2007;Friedlaender et al 2008;Novembre et al 2008;Segurel et al 2008;Reich et al 2009;Tishkoff et al 2009). Although population structure can give important information on the demographic history of a species and may lead to better understanding of evolutionary processes, population structure may also complicate certain investigations.…”
mentioning
confidence: 99%
“…There is no direct estimator available for these sex-specific effective population sizes, but F ST is a product of the effective population size and the sex-specific migration rate. It has been previously shown that when F ST A > F ST X-, the effective number of females is significantly higher than that of males, whatever the pattern of sex-specific dispersal (Segurel et al 2008). Verdu et al (2013) formally demonstrate that for F ST X :F ST A ratio < 1, male effective population size is smaller than that for females, regardless of any sex-specific migration (Verdu et al 2013 .…”
Section: Resultsmentioning
confidence: 86%